Q: X plus 6 9

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

9 + 6% = 9 x (1 + (6/100)) = 9 x 1.06 = 9.54

The value of x can be determined by subtracting 6 from 9.

In the equation x + 9 = 6, x is negative.

x2 + 5x + 3 = 9 x2 + 5x - 6 = 0 (x + 6)(x - 1) = 0 x = -6 or x = 1

6 + 9 + 12 x 5 = 75 (The multiplication is done first)

Related questions

Find the solution for 4+6(X+9)

(6 x 9) + 6 + 9 = 69

9 + 6% = 9 x (1 + (6/100)) = 9 x 1.06 = 9.54

9

The value of x can be determined by subtracting 6 from 9.

In the equation x + 9 = 6, x is negative.

x2 + 5x + 3 = 9 x2 + 5x - 6 = 0 (x + 6)(x - 1) = 0 x = -6 or x = 1

x2 + 7x + 9 = 3 ∴ x2 + 7x + 6 = 0 ∴ (x + 6)(x + 1) = 0 ∴ x ∈ {-6, -1}

6 + 9 + 12 x 5 = 75 (The multiplication is done first)

-6

X + 3 = 9 x + 3 - 3 = 9 - 3 x = 6

X equals 9.